2021
DOI: 10.3389/fimmu.2021.671904
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of PET/CT in Combination With Regulatory B Cells for Therapeutic Response and Survival in Contemporary Patients With Newly Diagnosed Multiple Myeloma

Abstract: To assess patients with multiple myeloma (MM), the whole-body positron-emission tomography/computed tomography (PET/CT) occupies a pivotal position for diagnostic stratification, response evaluation, and survival prediction, while important limitations are recognized as incapable of representing tumor microenvironment. Regulatory B cells (Bregs) have been reported to have an inhibitory immune function, contributing to bone marrow (BM)-immunosuppressive microenvironment for MM. Therefore, to investigate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…This study also confirmed that for elderly patients with MM, the proportion of BM‐derived Bregs is related to the OS, while the proportions of Bregs and SUVmax were significantly associated with OS but not PFS, which was similar to our previous studies 19 . It may indicate that Bregs may negatively affect survival independent of tumor progression, and OS was valued as a more critical cancer trial outcome compared with PFS 35 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study also confirmed that for elderly patients with MM, the proportion of BM‐derived Bregs is related to the OS, while the proportions of Bregs and SUVmax were significantly associated with OS but not PFS, which was similar to our previous studies 19 . It may indicate that Bregs may negatively affect survival independent of tumor progression, and OS was valued as a more critical cancer trial outcome compared with PFS 35 .…”
Section: Discussionsupporting
confidence: 89%
“…This study also confirmed that for elderly patients with MM, the proportion of BM‐derived Bregs is related to the OS, while the proportions of Bregs and SUVmax were significantly associated with OS but not PFS, which was similar to our previous studies. 19 It may indicate that Bregs may negatively affect survival independent of tumor progression, and OS was valued as a more critical cancer trial outcome compared with PFS. 35 Bregs, a population of suppressor B cells, were initially described in autoimmune disease and much progress has been made to characterize their phenotype and function in the tumor microenvironment over the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the percentage of CD19+CD24 high CD38 high Bregs in MM patients decreased after treatment with daratumumab ( 113 ). Furthermore, the Breg combination with PET/CT can predict the therapeutic response and survival in contemporary patients with NDMM ( 114 ). Thus, Bregs also display the yin and yang effect in MM ( Figure 2 , Table 1 ).…”
Section: The Yin and Yang Effects Of Immune Cells Associated With Mul...mentioning
confidence: 99%